Effect of the use Extracts of some Plants to Control Fusarium.oxysporum f.sp. cucumerinum Causing root rot cucumber disease - Marzook Hussain, Entesar; Hassan Hadi, Duaa (Al-Qadisiyah Journal of Pure Science, 2018)
The aim of this study is to know the active influence of some extracts plants which include the extraction of Monterey cypress leaf, Christs thorm , Eucalypts and Oleander in four different concentration in every extraction plant 10%, 20%, 30%, 40% for control Fusarium oxysporum fungus caused root rot cucumber disease . The results appear that all the extraction plants which are used made a inhibition in the growth rate of the fungi . The 40% concentration is more efficiency ,the growth rate is 4, 3.75 , 2.75 ,2.12 Cm respectively and the inhibition rate is 52.94%, 55.88%, 67.64%,75.05% respectively. compared to the control treatment (F.oxysporum only) was growth rate 8.5cm. The most actively plant to reduce the growth of the fungi is the extraction of Oleander plant in the 40% concentration which made the inhibition rate 75.05%. The lowest rate of concentration to reduce the growth of the fungi is 10%.The inhibition rate is 25.05%,23.52%,28%,51.52%respectively.